Analisis Hukum Kasus Penyelundupan Emas Yang Dilakukan Pejabat Diplomatik Korea Utara Untuk Bangladesh Ditinjau Dari Vienna Convention On Diplomatic Relations 1961 - Kevin Tobing; Idris Idris (DE LEGA LATA: JURNAL ILMU HUKUM, 2021)
It is generally accepted diplomatic envoys have such immunities and privilege that comprise criminal, private and administrative jurisdiction in the interest of continuity of diplomatic mission. Immunities and privilege that diplomats have are given by reciprocity principle. Although in reality, immunities and privilege that diplomats have are usually used for their vested interest. Vienna Convention on Diplomatic Relations 1961 solely rules the sanction to foreign diplomats who have committed violation of national law of the receiving state, but it does not provide settlement of dispute upon those violation. Even though diplomats have such immunities and privilege, but those immunities and privilege are not absolute and the proceeding of those immunities and privilege must be followed base on Vienna Convention on Diplomatic Relations 1961. International law provides peacefully dispute settlement relating to the intention of diplomatic relations. Through various method provided by international law, the parties could choose any method or process of dispute settlement which agreed by the parties.